The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10734-008-9113-9
|View full text |Cite
|
Sign up to set email alerts
|

“Do I need research skills in working life?”: University students’ motivation and difficulties in quantitative methods courses

Abstract: This study explored university students' views of whether they will need research skills in their future work in relation to their approaches to learning, situational orientations on a learning situation of quantitative methods, and difficulties experienced in quantitative research courses. Education and psychology students in both Finland (N = 46) and the USA (N = 122), who thought that they would need research skills in their future work, differed significantly from the students who were not sure whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 28 publications
2
71
0
4
Order By: Relevance
“…Here, it is noted that the active support of colleagues not teaching quantitative methods is needed in order to positively challenge students' misconceptions concerning the value and role of 'numbers analysis' within their degree subject and for graduate employment. This would also serve to decrease their anxiety and increase their confidence in their ability to complete numeric study tasks, including conducting a statistical analysis (Murtonen et al, 2008). Finally, existing work recommends that universities provide additional mathematical and statistical skills support services for students who struggle to grasp key statistical concepts and procedures relevant to undertaking quantitative research (Matthews et al, 2012).…”
Section: Counting Better? An Examination Of the Impact Of Quantitativmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, it is noted that the active support of colleagues not teaching quantitative methods is needed in order to positively challenge students' misconceptions concerning the value and role of 'numbers analysis' within their degree subject and for graduate employment. This would also serve to decrease their anxiety and increase their confidence in their ability to complete numeric study tasks, including conducting a statistical analysis (Murtonen et al, 2008). Finally, existing work recommends that universities provide additional mathematical and statistical skills support services for students who struggle to grasp key statistical concepts and procedures relevant to undertaking quantitative research (Matthews et al, 2012).…”
Section: Counting Better? An Examination Of the Impact Of Quantitativmentioning
confidence: 99%
“…Falkingham and McGowan, 2012;Linden, 2012;Murtonen and Lehtinen, 2003) as well as what the student response is to attempts to broaden quantitative method teaching provision and introduce numbers and numeric study tasks more generally within the curriculum (e.g. Carey and Adeney, 2009;Murtonen et al, 2008).…”
Section: Counting Better? An Examination Of the Impact Of Quantitativmentioning
confidence: 99%
“…The students' beliefs and views about statistics may determine the extent to which they are anxious about it and may determine their ways of learning (Murtonen et al 2008). Students who consider research skills important for their future career tend to have a low level of statistics anxiety and use a deep learning approach to solve problems (Murtonen et al 2008).…”
Section: Worth Of Statisticsmentioning
confidence: 99%
“…These factors can affect the students' level of engagement, motivation and success in their learning (Murtonen et al 2008, Ramos & Carvalho 2011. The research literature has suggested that teaching quantitative skills through substantive, subject-based content (rather than directly introducing abstract quantitative content) can help reduce anxiety and frustration (Bridges et al 1998, Jackson & Johnson 2013.…”
Section: Introductionmentioning
confidence: 99%